Does early skin-to-skin contact have a long-term effect on the emotional and behavioral development of very preterm infants? - Trautmann-Villalba, Patricia; Heine, Eva; Kribs, Angela; Mehler, Katrin (Frontiers in Psychology, 2024)
Introduction Premature birth may impair a sensitive, responsive, enjoyable, and regulating parenting style, potentially leading to behavioral, cognitive, and emotional deficits in children. Additionally, the emotional bond between the parent and infant may be disturbed due to the restrictions and difficulties at the neonatal intensive care unit (NICU), further negatively impacting child development. Skin-to-skin contact (SSC) directly after birth is strongly recommended also for preterm or low birth weight infants since there is high-certainty evidence that SSC has positive effects on neonatal and maternal health as well as on the quality of the parent–child relationship. The aim of this study was to examine the effect of skin-to-skin contact immediately after childbirth on the development of emotional and behavioral problems in children born preterm entering school. Methods This study is part of a randomized controlled delivery room skin-to-skin study (Deisy Study). A total of 33 children (aged 6–8 years) were assessed at school start. The German version of the CBCL/6-18R was used to evaluate the presence of behavior problems. Results The perceived parental stress 6 months after discharge was the variable that most contributed to the variance explanation. SSC immediately after childbirth was not significant in the prediction of emotional and behavioral problems at school start. Limitations The study was conducted in a small study group. Partners' variables were not included. Information regarding sociodemographic variables and bonding quality was collected 6 months (corrected age) after birth. The measurement of children's behavioral problems is not objective and corresponds to the parents' perception. Clinical Trial Registration https://clinicaltrials.gov, deisy study NCT01959737, deisy follow up NCT03366285.